THE ROLE OF INFORMATION TECHNOLOGIES IN PREVENTING EPIDEMICS - Atakhanov Sanjar; Ma’rufov Faridun (Bright Mind Publishing, 2025)
In recent years, the global health system has faced significant challenges posed by major epidemics and pandemics. In particular, the COVID-19 pandemic vividly demonstrated the negative consequences of the rapid spread of diseases. These situations have shown that traditional methods are insufficient for controlling epidemics, and that the deep integration of digital technologies into the medical field is a necessity of the time. This article provides an in-depth analysis of the role of modern information technologies — such as artificial intelligence, big data analytics, geographic information systems (GIS), mobile applications, telemedicine, and other innovative tools — in forecasting epidemics, early detection, monitoring, and effective management. These technologies not only enhance the efficiency of the healthcare system but also serve as a strategic tool in safeguarding human health. Additionally, the article discusses the potential of these technologies, their pressing issues, and scientifically-based proposals for solving them.